Construction of a carbon neutral enterprise environmental performance assessment model based on transformer-GRU - Chen, Yanqing (Frontiers in Ecology and Evolution, 2023)
Carbon-neutral enterprise environmental performance assessment is a method to evaluate the impact and benefits of enterprises on the environment in the process of realising carbon neutrality. The evaluation content includes the enterprise's carbon emissions, energy consumption, wastewater and gas discharge, and solid waste treatment. This paper introduces a method for evaluating the environmental performance of carbon-neutral enterprises based on the Transformer-GRU model. The method proposed in this paper combines Transformer and GRU models, which can accurately predict and analyse the environmental performance of carbonneutral enterprises. This method uses the Transformer model to extract features. Then it combines the GRU model for sequence modelling, which can effectively improve the model's prediction accuracy and generalisation ability. At the same time, this paper also uses actual enterprise data for experimental verification. Experiments prove our proposed method's application value and practical significance in evaluating carbon-neutral enterprise environmental performance.